Pemasyarakatan Narapidana: Melihat Kembali Ke Pemikiran DR. Sahardjo - Petrus Irwan Panjaitan (GEVANGENEN Jurnal Pemasyarakatan, 2025)
Treating prisoners well and properly in a humane manner is one measure of whether a country is civilized or not, especially if the country is a country based on law like Indonesia. Indonesia as a country of law certainly no longer emphasizes the implementation of punishment as it once did during the colonial era, where Sahardjo said very seriously as in his speech "Pancasila Law Protection Banyan Tree Manipol/Usdek" where in addition to presenting National law, which is depicted by a banyan tree that symbolizes protection, he also expressed his views on the banyan tree, as an instructor for officers in treating prisoners, so that the purpose of imprisonment by him was formulated as in addition to causing suffering to the convict because of the loss of freedom of movement, guiding the convict to repent, educating him so that he becomes a useful member of Indonesian socialist society, understanding Sahardjo's thoughts, it is clear that imprisonment is no longer for retribution but for correctional, which sees prisoners as social beings who have the opportunity to repent, and can be accepted by society and become useful people. Sahardjo's thoughts led to the integration of prisoners, officers and society. Correctional facilities are not just about rehabilitating and resocializing prisoners, but also creating a restoration of social relations between prisoners and the community in the form of accepting former prisoners back after serving their sentences.